PENGEMBANGAN MOFIFIKASI ALAT KECEPATAN TENDANGAN TAEKWONDO - Murniwati, Murniwati; Supriatna, Eka; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to develop new innovations in the form of electronic media that can add effectiveness to the Borneo Spirit Clab taekwondo kick measurement process.Research development or Research and Development (R&D). The research approach used in this research is procedural. The trial subject in this study was the Borneo Spirit Clab.The results of the study were questionnaires that had been validated and tested. The results of the validation by the material experts received the category